Gene expression network analysis of the routes to pluripotency - Amaral, Fabio M R (2018)
Great progress has been made towards the understanding of the molecular mech- anisms driving factor induced somatic cell reprogramming to pluripotency since the discovery by Takahashi and Yamanaka. However this process remains highly stochastic and inef cient. More study is needed in order to achieve a more de- terministic cell fate conversion which could further improve the quality of stem cells generated, essential for prospective therapeutic applications. The work presented here was developed under the premise that natural embryonic devel- opment can serve as a guide to achieve more ef cient pluripotency induction. It was observed that the histone variant H2A.Z, which has a role in pluripotency in embryonic stem cells, is highly expressed in the oocyte and upon over-expression, together with Pou5f1, Sox2, Klf4 and Myc, was able to increase the ef ciency of somatic cell reprogramming to induced pluripotency. A gene co-expression network analysis of somatic cells being reprogrammed identi ed hub genes as- sociated with H2Af.z and chromatin remodelling related genes which could be tested for further improving the reprogramming ef ciency induced by H2Af.z over-expression. Moreover, the study of genetic networks from pre-implantation embryos identi ed preserved genetic circuits also present during the course of reprogramming. The most preserved network modules are associated with the nal stages of pluripotency induction. However the analysis also identi ed a genetic network associated with the zygotic genome activation in the totipotent embryo stage which is also found in a sub-population of pluripotent stem cells characterised by the expression of genes from the Zscan4 family, Tet1, Etv5 and Mga among other genes. This provocative observation led me to hypothesise that during the course of reprogramming the forced activation of hub genes from such network may help improve its ef ciency, possibly by recapitulating the natural embryonic processes which induces totipotency prior to pluripotency. The identi- cation of preserved network modules and its hub genes presented in this work may serve a platform for further reprogramming studies in a quest for improved cocktails of reprogramming factors capable of more ef ciently generating induced pluripotent stem cells.